Spinal Anesthesia Failure In Patients With Total Abdominal Hysterectomy With Anemia and Its Management: Case Report - I Gede Catur Wira Natanagara; I Komang Budi Lastiawan (Jurnal Health Sains, 2022)
A 46-year-old woman with a diagnosis of uterine myoma and anemia who will undergo an elective total abdominal hysterectomy by an obstetrician and gynecologist. The patient has received PRC transfusion, fasted for 8 hours and is hemodynamically stable. Preoperative vital signs showed blood pressure: 130/80 mmHg, pulse: 64 times/minute, respiration: 20 times/minute, and 97% oxygen saturation without supplemental oxygen. Spinal anesthesia technique was performed with the patient lateral decubitus position at L3-4, CSF (+), blood (-), Bupivacaine 0.5% hyperbaric 15 mg and then the patient was positioned back in the supine position. A pin prick test was performed to find that there were no sensory and motor blocks, spinal anesthesia was performed again in a sitting position, at L3-4, CSF (+), blood (-), Bupivacaine 0.5% hyperbaric 15 mg and returned to position. supine. Evaluated by pin prick test and still no sensory and motor block. The block failed and was converted to general anesthesia with ETT. The duration of the operation is 2 hours, during observation in the recovery room the patient can be treated in the room.